Partners in Development: Three Sectors of Society State, Business and NGO - Rahman, Mustaghis ur (JISR management and social sciences & economics, 2004)
Ideally, social development is a prime duty of state. However in developing countries, the importance of business and NGO sectors, and limitations of state in realizing the social ideals cannot be ignored. Each sector has immense potentialities in their respective field, such as: state can provide enabling environment and space for the other two sectors; business can solve the financial problems for the government’s agenda of development; and NGOs can implement the development agenda of government more economically and efficiently at the grass root level. The partnership for social development can bebuilt on both - the strength and weakness of the three sectors of society. For the purpose there is a need to understand the nature, character, strengths and weaknesses of the three sectors. This study especially focuses on the dynamics of the three sectors with reference to Pakistan in order to provide a basis to state and other two sectors to become partners in social development.